Prevalence and correlates of violence among sexual and injecting partners of people who inject drugs living with HIV in Kenya: a cross-sectional study - Sai Win Kyaw Htet Aung; Hanley Kingston; Loice W. Mbogo; Betsy Sambai; Aliza Monroe-Wise; Natasha T. Ludwig-Barron; David Bukusi; William Sinkele; Esther Gitau; Sarah Masyuko; Joshua T. Herbeck; Carey Farquhar; et al. (BMC, 2023)
Abstract Background In Kenya, violence is common among people who inject drugs (PWID) living with HIV and their sexual and injecting partners and may lead to decreased uptake of HIV services, increased HIV risk behaviors, and increased HIV transmission. Violence is defined as any physical harm, threatened harm, or forced sexual acts inflicted on a person in the past year. Understanding the nature of violence and its correlates among PWID and their partners will inform population-specific public health interventions and policy recommendations. Methods This is a cross-sectional study nested in a prospective cohort study conducted in eight public health centers, methadone clinics, and needle syringe programs in Nairobi, Kilifi, and Mombasa counties in Kenya. 3,302 sexual and/or injecting partners of PWID living with HIV were recruited through assisted partner services and participated in the study. Prevalence and correlates of violence were identified using the Wald test and negative binomial regression. Results Out of 3302 study participants, 1439 (44%) had experienced violence within the past year. Physical violence was the most common form of violence experienced (35%), followed by being threatened (23%) or subjected to sexual violence (7%). In an adjusted analysis, female participants reported higher experiences of sexual violence (prevalence ratio [PR] = 2.46; 95% confidence interval [CI] 1.62, 3.74; p < 0.001) compared to male participants. In adjusted analysis, coastal residents had a higher experience of overall violence (PR = 1.48; 95% CI 1.27, 1.72; p < 0.001) than those living in Nairobi. This regional effect was relatively stronger among the female respondents (p interaction = 0.025). Participants' sex modified the association between region and experiencing violence after adjusting potential confounding factors. Conclusions The study reveals the prevalence of violence among PWID and identifies high-risk sub-groups, including women, specifically for sexual violence, and coastal residents. Tailored interventions addressing their unique needs are essential. A holistic approach that combines violence prevention and response, comprehensive harm reduction, healthcare access, and community support is crucial to address the complex issue of drug use and HIV burden among PWID in Kenya for improved health outcomes.